The Functional Role of Hyperpolarization Activated Current (If) on Cardiac Pacemaking in Human vs. in the Rabbit Sinoatrial Node: A Simulation and Theoretical Study - Bai, Xiangyun; Wang, Kuanquan; Boyett, Mark R.; Hancox, Jules C.; Zhang, Henggui (Frontiers in Physiology, 2021)
The cardiac hyperpolarization-activated “funny” current (If), which contributes to sinoatrial node (SAN) pacemaking, has a more negative half-maximal activation voltage and smaller fully-activated macroscopic conductance in human than in rabbit SAN cells. The consequences of these differences for the relative roles of If in the two species, and for their responses to the specific bradycardic agent ivabradine at clinical doses have not been explored. This study aims to address these issues, through incorporating rabbit and human If formulations developed by Fabbri et al. into the Severi et al. model of rabbit SAN cells. A theory was developed to correlate the effect of If reduction with the total inward depolarising current (Itotal) during diastolic depolarization. Replacing the rabbit If formulation with the human one increased the pacemaking cycle length (CL) from 355 ms to 1139 ms. With up to 20% If reduction (a level close to the inhibition of If by ivabradine at clinical concentrations), a modest increase (~5%) in the pacemaking CL was observed with the rabbit If formulation; however, the effect was doubled (~12.4%) for the human If formulation, though the latter has smaller If density. When the action of acetylcholine (0.1 nM) was considered, a 20% If reduction markedly increased the pacemaking CL by 37.5% (approximating a 27.3% reduction in the pacing rate), which is similar to the ivabradine effect at clinical concentrations. Theoretical analysis showed that the resultant increase of the pacemaking CL is inversely proportional to the magnitude of Itotal during diastolic depolarization phase: a smaller If in the model resulted in a smaller Itotal amplitude, resulting in a slower pacemaking rate; and the same reduction in If resulted in a more significant change of CL in the cell model with a smaller Itotal. This explained the mechanism by which a low dose of ivabradine slows pacemaking rate more in humans than in the rabbit. Similar results were seen in the Fabbri et al. model of human SAN cells, suggesting our observations are model-independent. This study explains why low dose ivabradine at clinically relevant concentrations acts as an effective bradycardic agent in modulating human SAN pacemaking.